Listening to stories of study: identity and the awarding gap experienced by Ethnic Minority students in the context of distance education. (3rd April 2023) - Rai, Lucy; Simpson, Jennifer
ABSTRACT: The disproportionately low degrees awarded to Ethnic Minority students are stark, representing an enduring challenge across the entire higher education sector including distance education. This paper reports on a study conducted in a distance learning university in the UK which employed a mixed-methods approach to explore the experiences of Ethnic Minority students. The paper draws on the concept of 'over-efforting' and research undertaken by Stevenson into personal educational histories. The methodology included quantitative analysis to provide a broad context with additional qualitative analysis of three case studies to provide rich, deep data. In combination, these data enable the authors to explore the significance of personal educational histories to understand the individual experiences of three students within the context of broader quantitative patterns. The paper offers some insights into these experiences in order to raise important questions about the impact of identities and personal educational histories on participating in tuition within the context of distance education.